Antichrist in the Middle Ages: Plus ça change… - Ryan, Michael A. (History compass, 2009)
Throughout the entirety of the European Middle Ages (ca. 500-1500 C. E.), Christianity functioned as a dominant force in political, social, and cultural matters, replete with figures both natural and supernatural. One of the most fascinating, and widely studied, individuals within the Christian worldview was the Antichrist. An entirely human, yet utterly evil, foil to Jesus Christ within Christian understanding, the Antichrist was the central figure whose advent would begin the various traumas of the Apocalypse and usher in the End Times. Although a terrible and traumatic figure, the Antichrist’s humanity is key to understanding him, as the name ‘Antichrist’ as applied to various individuals appears repeatedly throughout the Middle Ages in response to historic moments of crisis. Modern scholars in the fields of history, art history, and literature have recognized that the Antichrist’s mutability is crucial for comprehending him within the medieval context, as he served as a way to call for ecclesiastical reform or to criticize one’s political enemies. Scholars recently have begun to take note of medieval approaches to resisting the Antichrist. One of the most important tools at medieval people’s disposal was in the form of the occult sciences, such as astrology or alchemy. The Antichrist was thus more than just a shadowy and fearsome figure lurking in the darkness, but proved to be a central figure that drove intellectual, cultural, and religious matters alike during the Middle Ages.